Respon Suhu pada Laju Pengeringan dan Mutu Manisan Mangga Kering (Mangifera indica L.) - Rozana -; Rokhani Hasbullah; Tjahja Muhandri (PERTETA, 2016)
AbstractMango is higly perishable and must be consumed within a few days after harvesting. Preserving mango into dry product can extend shelf life and increase added value. The research aimed to investigate the processing technology of dried candied mango by analysing the drying rate and quality of the product in various drying temperature and slice forms the mango. Mangos of Kopek cv. were sliced into cubes, bar, and flat then dried at 45°C and 50°C. Responses which observed were drying rate, water content, water activity value (aw), yield, and organoleptic. The results showed that the drying rate fluctuates due to the influence of the opening of the drying rack and the heating element. Shortest drying time is obtained in the form of slices drying box at 50°C with a yield of 52.45% and the value of aw 0.59. Organoleptic response indicates that the wedge shape and drying temperature does not affect the assessment of panel.AbstrakBuah mangga sangat mudah rusak dan harus dikonsumsi dalam beberapa hari setelah panen. Mengawetkan mangga menjadi produk kering mampu memperpanjang umur simpan dan meningkatkan nilai tambah. Penelitian ini bertujuan untuk mengkaji teknologi pengolahan manisan mangga kering dengan menganalisis karakteristik pengeringan pada berbagai suhu pengeringan dan bentuk irisan mangga. Buah mangga varietas kopek diiris menjadi bentuk kubus, balok, dan pipih kemudian dikeringkan pada suhu 45°C dan 50°C. Respon yang diamati meliputi laju pengeringan, kadar air, nilai aw, rendemen, dan organoleptik. Hasil penelitian menunjukkan bahwa laju pengeringan berfluktuasi karena pengaruh pembukaan rak pengering dan elemen pemanas. Waktu pengeringan terpendek diperoleh pada pengeringan bentukirisan kubus pada suhu 50°C dengan rendemen sebesar 52.45% dan nilai aw 0.59. Respon organoleptik menunjukkan bahwa bentuk irisan dan suhu pengeringan tidak mempengaruhi penilaian panelis.